Yes-associated protein and transcriptional coactivator with PDZ-binding motif as new targets in cardiovascular diseases. (September 2020) - Yu, Yue; Su, Xingli; Qin, Qiaohong; Hou, Ying; Zhang, Xin; Zhang, Hongmei; Jia, Min; Chen, Yulong
Graphical abstract: Abstract: As transcriptional co-activators, Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) can regulate cell proliferation, migration, differentiation, and apoptosis by interacting with the transcription factors [e.g., transcriptional enhancer associate domain (TEAD) family members]. Polarity and junctional proteins, mechanical stress, and G protein-coupled receptors (GPCRs) are Hippo pathway-dependent upstream regulatory pathways of YAP and TAZ activity. In addition, posttranslational modifications (such as phosphorylation, O-GlcNAcylation, acetylation, methylation, geranylgeranylation, and palmitoylation) also participate in the regulation of YAP and TAZ activity. YAP and TAZ have recently been implicated in the pathological process of vascular and heart diseases. The activation of YAP and TAZ promotes atherosclerosis, angiogenesis, restenosis, pulmonary hypertension, myocardial hypertrophy, and myocardial fibrosis, whereas the inhibition of YAP and TAZ is involved in aortic aneurysms, aortic dissection, myocardial ischemia-reperfusion injury, and myocardial infarction. Thus, both YAP and TAZ may be potential targets for treating cardiovascular diseases. In this review, we discuss the latest findings regarding YAP and TAZ and the potential drugs that target these compounds to treat cardiovascular diseases. This review lays the foundation for a future direction of cardiovascular disease research.